= cos[x] ( 1- (1-2sin²[x]) )
= cos[x] (2sin²[x])
= sin[x] (2sin[x] cos[x])
= sin[x] sin[2x]
©
2007-09-02 00:23:51
·
answer #1
·
answered by Alam Ko Iyan 7
·
1⤊
0⤋
LHS
cos x [1 - (1 - 2 sin ² x) ]
cos x [ 2 sin ² x ]
sin x (2 sin x cos x)
sin x sin 2x
RHS
sin x sin 2x
LHS = RHS
2007-09-05 20:57:04
·
answer #2
·
answered by Como 7
·
0⤊
0⤋
ò(1-sin x)/(1+sin x) dx
= ò(1-sin x)2/(1-sin2x) dx
= ò(1 - 2 sin x + sin2x)/cos2x dx
= òsec2x dx - ò2 sin x/cos2x dx + òtan2x dx
= òsec2x dx - ò2 sin x/cos2x dx + ò(sec2x -1) dx
= tan x - 2 sec x + (tan(x)-x) + C
= 2 tan(x) - 2 sec(x) - x + C
This brings up another interesting identity
sec(x) - tan(x) = (1-tan(x/2))/(1+tan(x/2))
Proof: (1+tan²(x/2))/(1-tan²(x/2)) - 2 tan(x/2)/(1-tan²(x/2)), from the Weierstrass t-substitutions,
= (1-tan(x/2))²/(1-tan²(x/2))
= (1-tan(x/2)/(1+tan(x/2))
2007-09-02 00:21:15
·
answer #3
·
answered by Starz 2
·
0⤊
0⤋
use the sum formula for sine sin(90 +@) = sin90cos@ +sin@cos90 = (1)cos@ +sin@ (0) = cos@
2016-05-19 02:27:50
·
answer #4
·
answered by ? 3
·
0⤊
0⤋
1-cos(2x)=2 sin^2(x)
cos x(1-cos(2x) )=cos(x)*2*sin^(2)x
=cos(x)*2*sin(x)*sin(x)
2sin(x)*cos(x)=sin(2x)
using this in the above equation,
=sin(x)*sin(2x)
2007-09-02 00:29:16
·
answer #5
·
answered by MathStudent 3
·
0⤊
0⤋
take L.H.S cosx(2 sinx*sinx) =2(sinx)(sinx)(cosx)
(bcoz of formula 1-cos2x=2 sinx*sinx)
now take R.H.S sinx(2 sinx*cosx) (FORMULA=SIN2x=2 sinx cosx)
=2(sinx)(sinx)(cosx)
therefore L.H.S=R.H.S
2007-09-02 01:23:59
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋